Does financial leverage volatility induce systemic financial risk? Empirical insight based on the Chinese fintech sector. (9th November 2022) - Zheng, Zhiyong; He, Jian; Yang, Yingjie; Zhang, Mengting; Wu, Desheng; Bian, Yang; Cao, Jianhong
Abstract: Financial leverage volatility is a significant factor contributing to the formation of systemic financial risk, which is more apparent in China's fast‐growing fintech (financial technology) field. Using the Conditional Value‐at‐risk approach (ΔCoVaR) risk metric, the generalized autoregressive conditional heteroskedasticity (Structural Vector Autoregression with Stochastic Volatility model [SV‐TVP‐SAVR]) model, and the generalized forecast error variance decomposition (Tvpdy) model, this paper discusses how financial leverage volatility shocks fintech sectoral risks and the evolution of the risk within fintech under the shocks on the basis of the classification criteria of the Chinese fintech enterprise database and daily trading data of A‐share listed companies. The statistical results show that financial leverage volatility causes risk changes across fintech sectors, which is especially significant during economic downturns or government interventions. Also, under the shock of financial leverage volatility, the fintech sectors will absorb or diffuse risks outward through spillover channels, with significant differences in the risk spillover conditions of different types of sectors. Finally, the fintech sector can produce a contagion system with the Internet consumer finance, payment, and Internet microcommercial credit sectors as the core of risks, resulting in a systemic risk crisis. Our findings have major implications for Chinese regulators to balance financial leverage and prevent systemic risks in the fintech sector.